Transitioning Livelihood Strategies Among the Garo Community: A Case Study in Netrakona, Bangladesh (Journal of Population and Development, 2024)
Garo community is one of the greatest neglected instinctive communities of Bangladesh. The Garo people are neglected from their basic needs and it is significant to detect the situation and attitude to draw the real picture of them. This research work predominantly favors on the Garos livelihood pattern from past to present and to ascertain the alter of their livelihood. This study has conducted on the endemic community named Garo living within Durgapur and Kolmakanda upazila area of Netrakona district in Bangladesh. In doing so both historical and explorative data was applied; historical data was mostly procured from secondary sources such as revealed books, journals, articles, reports, census and souvenir. Qualitative research method was adopted for this study and 30 Garo people were chosen by using purposive sampling method for the study. The study uncovers that Garo’s traditional life practices are under the intimidation of the cancellation and over the motion of time they are acquiring completely a new life. In this research, the researchers have found several interior and exterior factors which are mainly accountable for Garo’s livelihood change. Ultimately, while the Garo community is switching then they are rejecting many of their characterized criterion and accommodating to some other livelihood criterion which are directly influenced by Christianity, NGOs, globalization and social development. As a result, many of Garos traditional cultures including language, food habits, dress pattern and even religion are under challenges. They need better communication and transportation system, more educational facilities, more government and non-government assistance including material and financial.